ANALISA PENGGUNAAN INTERNET TERHADAP PERKEMBANGAN PROSES BELAJAR SISWA (Studi kasus: siswa/siswi SMP dan SMU pada daerah sepatan tangerang selatan) - ROY IRAWAN (Universitas Bina Sarana Informatika, 2017)
Internet is one of the clearest evidence of rapid technological developments in the field of information and telecommunications. The Internet brings a huge influence in the pattern of life of the world community, especially the developed countries, This research was conducted in the southern area of Tangerang. The number of respondents is 30 students SMP and SMU in the area sepatan tangerang south. The instrument used in this study is questionnaire while the variables of concern in this study are independent variables (internet) (X1) and dependent (learning process) (Y). Researchers use validity test, reliability test, T-test, correlation coefficient and regression equation, result of research indicate that internet usage (X) have an effect on student learning process (Y) coefficient of determination value (R2) that is 0,032 which has the mean that influence of internet usage to learning process development is 3.2% and the rest influenced by other variables and also obtained Regression equation Y = 7,953 + 0,131X1, result from regression equation indicate that there is influence of internet usage toprogressof student learning process. Key word: Internet Usage, Student Learning Process